2000
DOI: 10.1007/s004670000457
|View full text |Cite
|
Sign up to set email alerts
|

Experimental intrauterine growth retardation alters renal development

Abstract: Vascular placental insufficiency is considered a common pathogenic factor in human intrauterine growth retardation (IUGR), resulting in small-for-gestational-age, asymmetric newborns. IUGR neonates experience higher morbidity and mortality rates, as well as a possible contribution towards late sequelae, such as hypertension, and cardiovascular disease in adulthood. To simulate vascular placental insufficiency, an experimental rabbit IUGR model was used. Intrauterine growth retardation was achieved by ligation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
81
0
3

Year Published

2004
2004
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(93 citation statements)
references
References 29 publications
9
81
0
3
Order By: Relevance
“…The induction of IUGR by UPE did not result in a reduction in the number of nephrons, which raises some interesting issues as to the influence of the timing of growth restriction. IUGR has been reported as causing a reduction in nephron numbers in rats (2, 3), rabbits (15), pigs (16), sheep (17), and even human infants (1). Surprisingly, in our study this was not the case when IUGR was induced by UPE.…”
Section: Discussionmentioning
confidence: 99%
“…The induction of IUGR by UPE did not result in a reduction in the number of nephrons, which raises some interesting issues as to the influence of the timing of growth restriction. IUGR has been reported as causing a reduction in nephron numbers in rats (2, 3), rabbits (15), pigs (16), sheep (17), and even human infants (1). Surprisingly, in our study this was not the case when IUGR was induced by UPE.…”
Section: Discussionmentioning
confidence: 99%
“…Different animal models include dietary undernutrition induced by global food restriction (9,10) or protein restriction during gestation (11,12,13,14,15), maternal hypoxia during gestation (16,17), placental insufficiency (18,19,20,21,22), or prenatal glucocorticoid treatment (23,24).…”
Section: Sex Differences In Fetal Programming: Animal Studiesmentioning
confidence: 99%
“…Nephron number is reduced in models induced by nutrimental insult in the rat (13,14,15), sheep (12), or microswine (47), and in models induced by placental insufficiency in the rat (21) and rabbit (19). Placental insufficiency in the rat leads to marked reductions in nephron number associated with significant increases in renal apoptosis and expression of key apoptosis genes and in the IUGR offspring (48).…”
Section: Mechanisms Of Fetal Programming Birth Weight Nephron Numbermentioning
confidence: 99%
“…In IUGR rat offspring, we and others have shown that early neonatal overfeeding or an elective neonatal high protein diet affect renal structure and functions as early as during the neonatal period with significant renal hypertrophy, renal overweight, proteinuria, and glomerular sclerosis (Bassan et al. 2000; Boubred et al. 2009, Luycks et al 2009).…”
Section: Introductionmentioning
confidence: 99%